Soft and smart modular structures actuated by shape memory alloy (SMA) wires as tentacles of soft robots. (19th July 2016) - Jin, Hu; Dong, Erbao; Xu, Min; Liu, Chunshan; Alici, Gursel; Jie, Yang
Abstract: This paper introduces the design and fabrication of a multi-layered smart modular structure (SMS) that has been inspired by the muscular organs and modularity in soft animals. The SMS is capable of planar reciprocal motion of bending in heating process and recovering in cooling process when SMA wires carry out phase transformation. An adaptive regulation heating strategy is applied to avoid overheating and achieve bending range control of the SMS based on the resistance feedback of the SMA wires which as actuator of the SMS. The SMS can modular assemble soft robots with multiple morphologies such as lateral robots, bilateral robots and actinomorphic robots. A five-armed actinomorphic soft robot is conducted to crawling in terrestrial ground (max speed: 140 mm s −1, 0.7 body s −1 ), swimming in underwater environment (max speed: 67 mm s −1, 2.5 height s −1 ) and griping fragile objects (max object weight: 0.91 kg, 15 times the weight of itself). Those demonstrate that the performance of the SMS is good enough to be modular units to establish soft robots which possess a high speed of response, good adaptability and a safe interaction with their environments.